New records of the invasive pest Drosophila suzukii (Matsumura) (Diptera: Drosophilidae) in the South American continent - Lavagnino, Nicolas Jose (2018)
The present study reports four new presences of Drosophila suzukii (Matsumura, 1931) (Diptera: Drosophilidae) in Argentina, extending the geographical range of this species in South America. This fly uses as breeding site mainly small soft-skinned fruits and there are reports from several parts of the world that it causes damage to commercial plantations generating economic losses to fruit producers. Of the new records one is registered in east Argentina near the previously reported presences in Brazil where the flies were captured around an orange orchard, one farthest from this point to the west collected from an unknown host and two other records were registered in raspberries plantations in Patagonia region at the southern part of the continent. In addition to the presences reported here for the first time, we present all previous reports of D. suzukii in South America as a review of the early stages of the invasion of this pest species to the continent. With the current data, there is evidence to pass from the status of unconfirmed or expected presence to an incipient confirmed presence of D. suzukii in southern latitudes of South America. This expansion of the spatial dimension of D. suzukii niche to areas where it was not previously found implies potential damages and economic losses for regional economies.